Newborn weight change and childhood cardio-metabolic traits - a prospective cohort study - Maria João Fonseca; Milton Severo; Debbie A. Lawlor; Henrique Barros; Ana Cristina Santos (BMC, 2018)
Abstract Background Newborn weight change (NWC) in the first 4 days represents short-term adaptations to external environment. It may be a key developmental period for future cardio-metabolic health, but this has not been explored. We aimed to determine the associations of NWC with childhood cardio-metabolic traits. Methods As part of Generation XXI birth cohort, children were recruited in 2005/2006 at all public units providing obstetrical and neonatal care in Porto. Birthweight was abstracted from clinical records and postnatal anthropometry was obtained by trained examiners during hospital stay. NWC was calculated as ((minimum weight - birthweight)/birthweight) × 100. At age 4 and 7, children were measured and had a fasting blood sample collected. Fasting glucose, LDL-cholesterol, triglycerides, waist circumference, systolic and diastolic blood pressure were evaluated. This study included 312 children with detailed information on growth in very early life and subsequent cardio-metabolic measures. Path analysis was used to compute adjusted regression coefficients and 95% confidence intervals. Results NWC was not associated with any cardio-metabolic traits at ages 4 or 7. Strong associations were observed between each cardio-metabolic trait at 4 with the same trait at 7 years. The strongest associations were found for waist circumference [0.725 (0.657; 0.793)] and LDL-cholesterol [0.655 (0.575; 0.735)]. Conclusions No evidence that NWC is related to childhood cardio-metabolic traits was found, suggesting that NWC should be faced in clinical practice as a short-term phenomenon, with no medium/long term consequences, at least in cardio-metabolic health. Our results show strong tracking correlations in cardio-metabolic traits during childhood.